Model Pembelajaran Dragon Ball Untuk Meningkatkan Hasil Belajar Matematika Siswa Di Wonogiri - Dwi Cahyani (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2022)
The background of the problem is that the results of students' mathematics learning in Wonogiri are not yet optimal. The aims of this study are (1) to describe learning activities during the implementation of the Dragon Ball learning model; (2) Describe the results of learning Mathematics with the Dragon Ball learning model. The research was conducted at SMPN 4 Satu Atap Kismantoro, Wonogiri Regency. The method used is a classroom action research approach. The results of the study of 20 students of SMPN 4 Satu Atap Kismantoro, Wonogiri Regency explained that student learning outcomes had increased, from the pre-cycle data 70%, in cycle 1 80% increased in cycle 2 it reached 90%. The study concluded that the improvement of students' mathematics learning outcomes by using the Dragon Ball learning model.